Umsetzung des datenschutzrechtlichen Auskunftsanspruchs auf Grundlage von Usage-Control und Data-Provenance-Technologien - Bier, Philipp Christoph Sebastian (Karlsruher Schriften zur Anthropomatik, 2021)
The ever-growing levels of complexity of modern information systems complicate the traceability of processed and stored personal data. The individual citizen is at the mercy of the systems. Data protection law tries to counteract this. The right to information is one instrument of data protection to establish transparency. This work critically evaluates the right to information and creates comprehensive technical preconditions for its exercise.